Measuring location and properties of very high frequency sources emitted from an aircraft flying through high clouds - Scholten, Olaf; Lourens, Marten; Buitink, Stijn; Cummer, Steve; Dwyer, Joe; Hare, Brian M.; Huege, Tim; Liu, Ningyu; Mulrey, Katie; Nelles, Anna; Sterpka, Chris; Trinh, T. N.Gia; et al. (Nature Communications, 2025)
While broadband short-duration radio pulses from airplanes are commonly detected and used for calibration or as background in astrophysical observations, the precise locations of the emission regions cannot be determined in these studies. We show that it is possible to locate the few places on the body of an airplane, while it is flying through high clouds, from which broad-band, pulsed, radiation is emitted at very high frequency radio frequencies. This serendipitous discovery was made whilst imaging a lightning flash using the Low-Frequency Array (LOFAR). This observation provides insights into the way the airplane sheds the electrical charge it acquires when flying through clouds. Furthermore, this observation allowed us to test and improve the precision and accuracy for our lightning observation techniques. Our results indicate that with the improved procedure the location precision for strong pulses is better than 50 cm, with the orientation of linear polarization being accurate to within 25°. For the present case of a Boeing 777-300ER, very high frequency radio pulses were observed exclusively associated with the two engines, as well as a specific spot on the tail. Despite the aircraft flying through clouds at an altitude of 8 km, we did not detect any emissions from electrostatic wicks.
CRIS-Team Scopus Importer:2025-12-05